A Yolk–Shell Structured Silicon Anode with Superior Conductivity and High Tap Density for Full Lithium‐Ion Batteries. Issue 26 (20th May 2019) - Zhang, Lei; Wang, Chengrui; Dou, Yuhai; Cheng, Ningyan; Cui, Dandan; Du, Yi; Liu, Porun; Al‐Mamun, Mohammad; Zhang, Shanqing; Zhao, Huijun
Abstract: The poor cycling stability resulting from the large volume expansion caused by lithiation is a critical issue for Si‐based anodes. Herein, we report for the first time of a new yolk–shell structured high tap density composite made of a carbon‐coated rigid SiO2 outer shell to confine multiple Si NPs (yolks) and carbon nanotubes (CNTs) with embedded Fe2 O3 nanoparticles (NPs). The high tap density achieved and superior conductivity can be attributed to the efficiently utilised inner void containing multiple Si yolks, Fe2 O3 NPs, and CNTs Li + storage materials, and the bridged spaces between the inner Si yolks and outer shell through a conductive CNTs "highway". Half cells can achieve a high area capacity of 3.6 mAh cm −2 and 95 % reversible capacity retention after 450 cycles. The full cell constructed using a Li‐rich Li2 V2 O5 cathode can achieve a high reversible capacity of 260 mAh g −1 after 300 cycles. Abstract : Improving the conductivity and tap density of yolk–shell‐structured Si/C anodes for lithium‐ion batteries is possible by introducing Fe2 O3 nanoparticles (NPs) embedded in carbon nanotube (CNT) networks into the void space between the Si yolks and the outer double shell. A full cell can achieve a high reversible capacity of 260 mAh g −1 after 300 cycles.